2020
DOI: 10.1177/2516865720932146
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide DNA Methylation Patterns in Children Exposed to Nonpharmacologically Treated Prenatal Depressive Symptoms: Results From 2 Independent Cohorts

Abstract: Background: Maternal depressive symptoms are a common phenomenon during pregnancy and are related to negative outcomes for child development and health. Modifications in child DNA methylation are discussed as an underlying mechanism for the association between prenatal depressive symptoms and alterations in child outcomes. However, formerly reported genome-wide associations have yet to be replicated. Methods: In an epigenome-wide association study (EWAS), alterations of DNA methylation related to maternal pren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 94 publications
0
3
0
1
Order By: Relevance
“…We found that no replicated single significant CpG sites were reported from more than one study in any of the three categories (maternal depression, maternal depression treatment, and maternal anxiety). However, one CpG site, cg25157095 was found among the top non-significant CpG sites for maternal depression in two studies [40,47]. This CpG site is in an intron for the RIPK4 gene which has been implicated in keratinocyte differentiation, modulation of the actin cytoskeleton, and restricting intercellular adhesion [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that no replicated single significant CpG sites were reported from more than one study in any of the three categories (maternal depression, maternal depression treatment, and maternal anxiety). However, one CpG site, cg25157095 was found among the top non-significant CpG sites for maternal depression in two studies [40,47]. This CpG site is in an intron for the RIPK4 gene which has been implicated in keratinocyte differentiation, modulation of the actin cytoskeleton, and restricting intercellular adhesion [51].…”
Section: Discussionmentioning
confidence: 99%
“…2). Several articles described analyses of more than one exposure, resulting in 16 analyses [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] of maternal depression, 8 analyses [32,35,38,39,44,45,47,48] of maternal depression treatment, and 9 analyses [27,32,33,35,38,41,47,49,50] of maternal anxiety (Table S1). Based on STROBE and ROBINS-I criteria, we found that 13 analyses had a moderate risk of bias and 7 had a severe risk of bias (Tables S2 and S3).…”
Section: Included Studiesmentioning
confidence: 99%
“…Pero en algún estudio más reciente no se han hallado efectos significativos de la exposición Rev Neuropsiquiatr. 2023;86(1): [35][36][37][38][39][40][41][42][43][44] al estrés experimentado por la madre en la metilación neonatal de la sangre del cordón umbilical uterino (22) y se ha llegado a desafiar la hipótesis de que sucedan modificaciones consistentes de la metilación del ADN en niños expuestos a síntomas depresivos maternos prenatales (23).…”
Section: Influencias Sobre La Información Genética Heredableunclassified
“…12 , 16 More recently, EWAS studies have been conducted to examine prenatal depressive symptoms or stressful life events; however, these studies have not replicated the findings of candidate gene studies. 17 - 20 …”
Section: Introductionmentioning
confidence: 99%